Guidelines for the diagnosis of gestational diabetes mellitus - admin, admin (2018)
Gestational diabetes is the impaired metabolism of carbohydrates, of varying severity that begins or is first recognized during pregnancy. The search for diabetes in pregnancy should be done from the first level of care throughout pregnancy, present or no risk factors, according to available resources and should be done by the screening using a test Oral Glucose Tolerance (OGTT ) at 24-28 weeks gestation.